Mustad'afin dalam Al-Qur'an: Studi Tematik Atas Penafsiran Buya Hamka - Fathur Rozi, Rozi; Moh Sofyan Andrian, Andrian; Abdul Majid, Majid (Mahad Aly Al Fithrah, 2023)
This article aims to explore the articulation of mustad'afi>n that is actually desired in the Qur'an. According to most, this term is still interpreted as du'afa>', while in fact it has different meanings and purposes. In this article, the researcher uses the perspective of Buya Hamka's interpretation. From the interpretation of this local figure, revealing mustad'afi>n will often remind oneself of Indonesia's past during the colonial era. The mustad'afi>n are certainly different from the du'afa>'. Because, mustad'afi>n are groups who are oppressed by other groups, but in fact they still have power and are not poor like the du'afa>'. The oppressed are always found in every era. Because every turn of the time cannot be separated from the tragedy of domination over something. The oppressed themselves are not only from an economic point of view, but also from a scientific, physical and mental aspect, as well as faith and morals. A little observation of Buya Hamka's interpretation of the letter al-Nisa>'/4 verse 75, that there is an oppression that has occurred in the history of Muslims, where Muslims are under the control of the Meccan polytheists so they cannot migrate. Therefore, as fellow Muslims, it is fitting to help the oppressed by defeating the oppressors. It is a dedication to protect themselves and save the oppressed from oppression